Analysis Of the Relationship Between Big Data and Smart Governance in The Context of Achieving Sustainable Governance - Satriatama, Muhammad Tegar; Nurmandi, Achmad; Hardianti, Hardianti; Lawelai, Herman; Kasiwi, Aulia Nur (Journal of Indonesian Rural and Regional Government, 2025)
Big Data and Smart Governance are important components in achieving sustainable governance. This article explores the integration of Big Data in public administration and its role in improving government efficiency, transparency, and accountability through data-driven decision-making. While Big Data offers great opportunities, governments face a variety of challenges, including data privacy, security, and technology infrastructure issues. This article identifies these challenges and highlights the potential of Smart Governance in supporting sustainable development by leveraging technology to achieve environmental, economic, and social goals. Through a comprehensive analysis, this study presents policy recommendations to help governments and stakeholders make optimal use of Big Data in supporting more effective and sustainable governance. These findings highlight the long-term benefits of integrating Big Data in public administration to ensure equitable and sustainable development.